Educação musical em pesquisa-formação: a voz cantada e falada de professoras da educação infantil - Tomazi, Ana Carla Simonetti Rossato (2019)
This dissertation is linked to Research Line 4 - Education and Arts, Post-graduation in Education Program, Federal University of Santa Maria, FAPEM research group - Formation, Action and Research in Music Education and to Laboratory of Music Education of the Education Center (LEM / CE). In this study, I sought to understand how a process of Formation Research, mobilized by the use of the voice sung/spoken by teachers of Early Childhood Education, can potentialize the musical practices in the classroom. As specific objectives, I sought to understand the contributions of the group as a formative device and the musical experiences in the formative process of the teachers during the Formation Research. Furthermore, to understand how the voice can be resignified by the teachers in the process of musical and pedagogical-musical formation. The research was based theoretically and methodologically on the principles of Formation Research (JOSSO, 2010a, 2010b), when considering the transformation of the subject, for the author, consciential subject. The literature review was based on academic productions about the in-service teacher continuous formation (FCPS), based on the authors Moriconi (2017), Baptaglin, Rosseto and Bolzan (2014), Alvarado-Prada, Freitas and Freitas (2010), among others, being deepened by the continuous formation in music (OLIVEIRA, 2016; MANZKE, 2016; ARAÚJO, 2012; FERNANDES, 2009; TARGAS, 2003). I also approached studies that dealt with Music Education linked to the Generalist Teaching in Childhood Education (STORGATTO, 2011, TIAGO, 2007, PACHECO, 2005, among others). For the production of data, I was guided by the oral and written formation narratives (CHIENÉ, 2010), by the narrative phases of Josso (2010b), triangulated to the eight formation meetings held with the teachers of Early Childhood Education, and to the three Times of Souza's (2014a) comprehension-interpretative analysis. Thus, the lived musical experiences, associated to the formation group, contributed to the formative process of the teachers and to the realization of more significant musical and pedagogical-musical practices in ECE's classrooms. It was possible to perceive awareness about the care, preparation and vocal exploration, which were reassigned by the teachers, in their teaching practices. I emphasize that the teachers who participated in the Formation Research did not do this as a simple course in which they "would gain things" but were involved in thinking about teaching in ECE and to resignify their practices and professional development. Finally, the results of this research will contribute to think about and promote significant formative movements, which will consider teachers as consciential subjects of formation, who have wishes, needs and educational desires.